英国儿童移植人群皮肤癌随访研究. (3rd December 2018) - Foo, S.H.; Nightingale, P.G.; Gazzani, P.; Bader, E.; Ogboli, M.; Martin‐Clavijo, A.; Milford, D.V.; Kelly, D.A.; Moss, C.; Thomson, M.A.
Abstract : Linked Article:  Foo et al. Br J Dermatol 2018;179 :1368–1375